Transformation of Gadget Use as Adaptive Learning Media Based on Deep Learning at Junior High School - Hartini; Daviq Chairilsyah; Rita Kurnia; Cindy Febby Anjana; Izadri Nizami; Noverman; Warni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
The use of gadgets in the environment is increasing, no longer limited to urban communities, but has spread even to remote villages. This study aims to analyze how gadgets are used as a medium for adaptive learning based on deep learning for students, teachers, and the principal, as the policymakers, in the SMPN 1 Cerenti environment. Deep learning-based adaptive learning is a digital instructional system that uses artificial intelligence to analyze behavioral data, learning speed, and student learning preferences in real time. Through interviews, observations, and documentation of students, teachers, and the principal, this study reveals that the use of gadgets as a medium for adaptive learning has both positive and negative impacts on the learning process. The use of gadgets as a medium for adaptive learning allows teachers to access digital platforms flexibly, to create an active, interactive learning ecosystem, and ensure that all task progress is monitored and well-structured. The use of gadgets in learning platforms still faces obstacles, such as limited school infrastructure, signal instability due to power outages, numerous students lacking supporting devices, and low digital literacy among senior teachers in accessing and operating learning platforms. The research results are expected to make a meaningful contribution to the transformation of education. These findings not only highlight the effectiveness of technology in creating a structured learning ecosystem but also provide concrete recommendations to overcome technical and cultural obstacles faced by students and teachers in the field. This research provides an alternative concrete solution for the standardization of personal learning at the junior high school level by utilizing gadgets as an adaptive learning medium, which can automatically and accurately bridge the gap in students' understanding in real time. This contribution is becoming increasingly crucial for schools in rural areas, as technology can bridge the gap in educational quality between rural and urban areas without absolute dependence on global connectivity.